Essentials of conversation analysis - Alexa Hepburn; Potter, Jonathan (America American Psychological Association, 2021)
The brief, practical texts in the Essentials of Qualitative Methods series introduce social science and psychology researchers to key approaches to qualitative methods, offering exciting opportunities to gather in-depth qualitative data and to develop rich and useful findings.In this book, Alexa Hepburn and Jonathan Potter provide an introduction to conversation analysis (CA), a qualitative approach that examines the actions and interactions that take place in face-to-face conversations, phone calls, texts, and various forms of media. This practical text illuminates how CA captures the subtleties of talk in interaction via an analysis of its elements and phases. The authors guide the reader through data collection, transcription, analysis, and writing papers, providing an invaluable starting point for researchers who wish to explore CA and get a foothold in its literature. About the Essentials of Qualitative Methods book series: Even for experienced researchers, selecting and correctly applying the right method can be challenging. In this groundbreaking series, leading experts in qualitative methods provide clear, crisp, and comprehensive descriptions of their approach, including its methodological integrity, and its benefits and limitations. Each book includes numerous examples to enable readers to quickly and thoroughly grasp how to leverage these valuable methods.
Keywords: Social interaction in primary groups